Quantitative evaluation of the time-course and efficacy of targeted agents for ulcerative colitis - Yu, Boran; Jin, Siyao; Han, Jiaqi; Xu, Jiamin; Zhang, Shaolong; Li, Yanming; Ma, Xiangyu; Wang, Xiaoling; Zhao, Libo (Frontiers in Pharmacology, 2024)
Background: Targeted agents were widely utilized in the treatment of ulcerative colitis (UC).Hence, a comprehensive understanding of the comparative drug efficacy in UC is of great importance for drug development and clinical practice. Our objective was the quantitative evaluation of comparative efficacy of targeted agents for UC.Methods: Three mathematical models were developed based on the data from randomized controlled trials in patients with moderate-to-severe UC to describe the time-course and doseresponse of efficacy defined as clinical remission, clinical response, and endoscopic improvement as well as placebo effect. The covariate effects were further evaluated. Model simulation was performed in a hypothetical population to compare the efficacies across different drugs.The analysis dataset was composed of data from 35 trials of 12 drugs in UC. Timeresponse relationships were evaluated, indicating a gradual onset of drug efficacy in adalimumab, ozanimod and Janus kinase (JAK) inhibitors. The dose-response relationships were estimated for each drug respectively. Patient's age, disease duration, baseline weight, prior tumor necrosis factor (TNF) exposure and current treatment with corticosteroid showed impact on the efficacy, which suggested that younger patients with shorter UC duration, without prior anti-TNF treatment and current corticosteroids therapy tended to get greater treatment effects.Conclusions: In this study, three longitudinal models for UC were developed to quantitatively describe the efficacy of targeted agents, as well as the influencing factors of the efficacy.Infliximab and upadacitinib were determined to be the most effective biologic and small targeted molecule, respectively. These findings may provide valuable implications for guiding future decision-making in clinical practice and drug development for UC.